Gestaltning och förverkligande av Icehotels utemiljö säsongen 2009/2010 - Julin, Elin (SLU/Dept. of Urban and Rural Development, 2010)
This paper constitutes graduate work at the landscape architecture program at the Department of Urban and Rural Development at the Swedish University of Agricultural Sciences, Uppsala. The main purpose of this paper is to create a project from an idea to reality. The place for the project is the environment of Icehotel in Jukkasjärvi in the north of Sweden. Icehotel is a unique hotel concept and each winter a hotel, a church and a bar is built at the area of only ice and snow, and each spring it all melts down and returns to the Torne river. During the project a plan for the environment, in ice and snow, will be made and then a part of it will be built in January 2010. The purpose is to improve the outdoor environment with landscape architecture to enhance the experience of Icehotel and create an exciting entrance to the area. During the project the whole process will be documented and evaluated. Icehotel is a very interesting area with many qualities but through different analyses many needs were discovered. With this knowledge I put together a vision for the project. The goal of the vision was to solve the needs and use the qualities. The biggest needs were to connect the important places, to enhance the main path, to make the entrance to the area clearer and more exciting and to hide the constructing area and its buildings. There was also a need to give the whole environment a structured expression. Through sketching and working with various kinds of models I created a concept and then a master plan before I travelled to Jukkasjärvi I January. During one and a half week I worked with building my proposal outside the reception at the entrance to the whole area and next to the Ice church and the Icehotel. The work was fun, giving and challenging. When the project at Icehotel was finished I investigated if I had succeeded with the goals I had put up for the area. I believe that my project has a meaning for the experience of the outdoor environment at Icehotel. The shapes I created frame and enhance the ...